A6.14 mTOR Directed Mesenchymal Tissue Response to Inflammation in Arthritis. (25th February 2013) - Karonitsch, T; Dalwigk, K; Glehr, M; Niederreiter, B; Steiner, CW; Smolen, JS; Kiener, HP; Superti-Furga, G
Abstract : Background: Accumulating evidence supports the concept that fibroblast-like synoviocytes (FLS) actively participate in the destructive, inflammatory process of rheumatoid synovitis. Thus, FLS frame a synovial microenvironment that augments and perpetuates synovial inflammation. Moreover, FLS, together with macrophages form an aggressive mass of cells ("pannus"), which invades and destroys the articular cartilage. The mechanistic target of rapamycin (mTOR) is best known for coupling energy and nutrient abundance to the execution of essential cellular processes, including cell growth and cell survival. More recent data indicate that mTOR directs the cellular response to inflammatory stimuli in cells of the immune system. It remains elusive, however, whether or not this also applies to mesenchymal cells, such as FLS in the context of rheumatoid synovitis. Materials and Methods: In order to assess mTOR activity by immunhistochemistry (IHC) as well as western blotting (WB), phosphospecific antibodies against mTOR (IHC) and mTOR substrates, including 4E-BP (IHC), AKT (WB), S6K1 (WB), and S6 (IHC) were used. To determine the functional significance of mTOR activity in FLS, Torin-1, a well defined, specific inhibitor of mTOR, was used. To establish a role for mTOR in the mesencyhmal, inflammatory tissue response, we used a previously described simplified 3-D model of the synovial tissue. IL-6 and IL-8 levels in the supernatants of 3-D cultures were measured by ELISA. Results: mTOR, 4E-BP and S6 were found to be phosphorylated in RA synovial tissues. These activated phospho-proteins were preferentially expressed in FLS, most prominently in the hyperplasic synovial lining layer. In-vitro, TNF stimulation of FLS resulted in the phosphorylation of AKT and S6K1, indicating that TNF activates the mTOR pathway in FLS. Stimulation of the 3D cultures with TNF resulted in hyperplasia of the lining layer at the surface of the spheres. Strikingly, treatment with Torin-1, prevented TNF induced lining layer hyperplasia. Unexpectedly, the combined treatment of 3-D cultures with TNF and Torin-1 resulted in increased production of IL-6 as well as IL-8 when compared to cultures that were solely exposed to TNF. Conclusions: These studies provide insight into the regulatory circuits that determine the synovial mesenchymal tissue response to inflammation and suggest a multifaceted role for mTOR in arthritis.